Nicotine Dependence from Electronic Cigarettes Use and Depressive Symptoms Among Adolescents - Winburn, Christopher; Ofei-Dodoo, Samuel (Kansas Journal of Medicine, 2023)
Introduction. The use of electronic cigarettes (e-cigarettes) has been increasing among adolescents in the United States population since they were first introduced to the US market in 2007. With depression as a major risk factor for suicide in adolescents, this study examined nicotine dependence from the use of e-cigarettes and depressive symptoms among adolescents.Methods. The authors conducted a retrospective patient chart review at a pediatric clinic in the Midwestern United States, from May 2021 to September 2021. As a standard practice, the clinic uses the adapted Penn State Nicotine Dependency Index to evaluate its patients’ nicotine dependence from the use of e-cigarettes and the PHQ-9 modified for teens to screen for depressive symptoms of its patients. Data on 69 patients were included in the study. The authors used standard descriptive statistics and an adjusted odds ratio (aOR) to analyze the data on the 69 adolescents. Results. The mean age of the adolescents was 17.6 (SD = 2.3), 46.4% (n = 32) were female, and 53.6% (n = 37) were male. More than 88% (n = 61) of the adolescents met criteria for high nicotine dependence from e-cigarette use and 30.4% (21 of 69) of them screened positive for depression. Findings of the mixed model analyses indicated that there was not a statistically significant association between nicotine dependence from e-cigarette use and depressive symptoms (aOR = 1.07; 95% confidence interval, 0.93-1.23; P = .0365).Conclusions. Our findings show that while a third of the adolescents screened positive for depression and the majority (88%) depended on nicotine from e-cigarettes, there was no association between the outcomes. Future larger multicenter studies are needed to better understand the association between nicotine dependence from e-cigarettes and depressive symptoms as reported in the literature.